NURSING ADVICE FOR THE DISCHARGE FROM HOSPITAL OF THE NEOPLAS-TIC PATIENT - Ieda Maria Leal da Cruz; Maria de Fátima Mantovani (Universidade Federal do Paraná, 2014)
This study, of the methodological type, aimed to elaborate systematized nursing advice for the discharge from hospital of the neoplastic patient. The model proposed for the guidance is based on Wanda Horta's Basic Human Needs Theory. The participants were 20 adult patients diagnosed with cancer, receiving treatment in an emergency care center at the teaching hospital in Curitiba, Paraná, in the period March - May 2013. The data were collected through semistructured interviews and, based on content analysis, the psychobiological, psychosocial and psychospiritual categories emerged, which formed the basis for the construction of 10 systematized items of advice. It is concluded that educational materials allow the nurse - among other benefits - to identify the patients' real needs, to evaluate the understanding of care advice, and consequently to contribute to the continuity of the treatment in the home.